Coded wireless communications over fading channels - Lau, Wee Leong. (2013)
This report presents the highlights of the studies and investigations on various channel models and various channel coding schemes. These studies aim to improve the system performance by adopting suitable channel coding schemes. Reviews on past research findings on different channel models and channel coding, particularly on additive white Gaussian noise (AWGN) channels or fading channels with error correcting codes will be presented. Theories of both the digital and wireless communication systems will be shown, especially into the understanding of different types of channel model and different types of channel coding.